MENINGKATKAN PRESTASI BELAJAR IPA MENGGUNAKAN MODEL CONTEXTUAL TEACHING AND LEARNING PADA SISWA KELAS IV SDN 1 NGRAHO KEDUNGTUBAN BLORA - Atalia Nur Ihsana Arafat (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2018)
The purpose of this research improves the student achievement of science (IPA) usingContextual Teaching And Learning (CTL) model in fourth grade students of SDN 1 NgrahoKedungtuban Blora Year 2017/2018. The type of research is Classroom Action Research(Penelitian Tindakan Kelas - PTK) with the research subject is the fourth grader of 14students and the research object is the implementation of learning to improve the studentachievement of science (IPA) by applying Contextual Teaching and Learning (CTL) model.The results of this research concluded that learning of science (IPA) using CTL model canimprove student achievement. Before action, the average student achievement of class isequal to 57 with a mastery of 27%. After action in the first cycle, the average studentachievement of class is increased to 76 with a mastery to 67% and increased again in thesecond cycle to 86 with a mastery of 100%. Based on the results of this research can beconcluded that the average of student achievement has increased by 23.2%..Keyword : learning outcomes, Contextual Teaching and Learning (CTL)Â